1965
DOI: 10.1042/bj0960027c
|View full text |Cite
|
Sign up to set email alerts
|

The Cytochemical Localization of Alkaline Phosphatase in Escherichia coli at the Electron-Microscope Level

Abstract: SHORT COMMIUNICATIONS 27c pronounced change in the ratio of the trans to the cw forms, with the concentration of the former always being several times greater than that of the latter. There was little evidence of double-bond migration under normal conditions. The conjugated linoleic acid and linolenic acid have retention volumes greater than those ofthe normal compounds and could be separated by gas-liquid chromatography (Daniels & Richmond, 1960). No conjugated linoleic acid and linolenic acid could be detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 7 publications
2
38
0
Order By: Relevance
“…In Bacterionema and Actinomyces, A1P and (or) its synthesis was inhibited by 10 mM Na2HP04 (Franker et al 1978), while in E. coli the synthesis of an inducible A1P was repressed in the presence of 2.3 mM Pi in the growth media (Done et al 1965;Torriani 1960). Cheng et al (1970~) and Hou et al (1966) found that, in P. aeruginosa, there was a 500-fold decrease in A1P activity in the presence of 7 mM Pi.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In Bacterionema and Actinomyces, A1P and (or) its synthesis was inhibited by 10 mM Na2HP04 (Franker et al 1978), while in E. coli the synthesis of an inducible A1P was repressed in the presence of 2.3 mM Pi in the growth media (Done et al 1965;Torriani 1960). Cheng et al (1970~) and Hou et al (1966) found that, in P. aeruginosa, there was a 500-fold decrease in A1P activity in the presence of 7 mM Pi.…”
Section: Discussionmentioning
confidence: 95%
“…The most extensively investigated periplasmic phosphatase has been Alp. In E. coli (Done et al 1965;Heppel 1967) and P. aeruginosa (Cheng et al 1970a(Cheng et al , 1970bCheng et al 1972), it is localized almost exclusively in the periplasm, being released in toto by mild cell disruption; in fact with few exceptions (Lindsay et al 1973;Work et al 1966), most of the periplasmic enzymes appear to be "free" in the cells periplasm. While the release of cell components from gram-negative bacteria into the surrounding milieu is known (Russell 1976), the kinetics of release of periplasmic enzymes during cell growth has not been extensively studied.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A number of experiments were carried out by either tetrazolium or tellurite techniques in bacterial dehydrogenase cytochemistry (16, 23,[26][27][28][29]. Only a few papers have been concerned with phosphatase location (3,13,30).…”
Section: Introductionmentioning
confidence: 99%
“…Done [4] studied the cytochemical localization of alkaline phosphat ase in Escherichia coli and found a remarkably well-defined compartmentalization. These observations were confirmed by Malamy and Horecker [15].…”
mentioning
confidence: 99%